No smoke without fire : cosmic dust emission as a tracer of star formation in galaxies - Bourne, Nathan (2013)
Studies of the history of the Universe are for a large part concerned with mapping the evolution of galaxies over cosmic time. Beginning from the seeds of density perturbations in the early Universe, and building up through gravitational and astrophysical interactions to form the wide diversity seen in the present day, galaxies allow us to observe the distribution of luminous (and dark) matter over a wide range of look-back times.